ВЛИЯНИЕ ОЗДОРОВИТЕЛЬНЫХ ПРОЦЕДУР НА ГЕМАТОЛОГИЧЕСКИЕ ПОКАЗАТЕЛИ У БЕРЕМЕННЫХ (Experimental biology, 2009)
Studying haematological parameters at the pregnant women, engaged by health promotion with use of natural factors was lead. It was shown, that health promotion procedures promote increase in quantity of blood cells. Thus normalization of a level of haemoglobin, decrease in desease by an anemia and activization of cellular and humoral immunity were observed.
Keywords: immunity; haematological parameters